Implementation of School Literacy Movement Program at the Level of Junior High School Education Units - Son, Aloisius Loka; Talan, Maria Rosalinda; Mone, Ferdinandus (Gema Wiralodra, 2023)
The School Literacy Movement (SLM) is a program designed to facilitate the acquisition of student literacy competencies. Schools that implement this government program will undoubtedly have an impact on the literacy abilities of their students, including reading literacy, scientific literacy, digital literacy, numeracy, and so on. This forms the basis for conducting research with the aim of describing the implementation of SLM in Junior High Schools throughout the Kefamenanu Sub-District. The respondents in this study include school principals, SLM administrators, library heads, Mathematics teachers, and Indonesian Language teachers. Data collection techniques employed are interviews and observation. Subsequently, data is analyzed using the flow model by Miles and Huberman, which involves data reduction, data presentation, data verification, and conclusion drawing. Findings from the research indicate that junior high schools in the Kefamenanu Sub-District have implemented SLM from the habituation stage to the development and learning stages; however, the implementation is inconsistent and not yet optimal. Thus, the execution of SLM requires maximum attention from stakeholders, involving teachers, parents, alumni, and community members.